(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
Today, companies should develop and operate in a sustainable and green society with the least possible negative environmental impact. At the global level, it is necessary to awaken and develop an awareness of the need to accept the concept of sustainable development, thus the application of the Corporate Sustainability Reporting Directive (CSRD) and ESG (environmental, social, and governance) concept. The Corporate Sustainability Reporting Directive (CSRD) is the new EU legislation requiring all large companies to publish regular reports on their environmental and social impact activities. CSRD sets out reporting requirements and obligations for companies and expands existing rules on non-financial reporting. CSRD reporting will help stakeholders (investors, consumers, policymakers, and others) evaluate large companies’ non-financial performance. This paper aims to explore the area of ​​sustainability reporting through CSRD reporting and its connection to the ESG concept in today’s business world.